2019
DOI: 10.1016/j.virusres.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biological characteristics of four novel recombinant avian infectious bronchitis viruses isolated in China

Abstract: A B S T R A C TInfectious bronchitis viruses (IBVs) of GI-13 (793/B) and GI-19 (QX/LX4) lineages have been frequently detected in China in recent years. Naturally recombinant IBVs originating from the GI-13 and GI-19 lineages have also been isolated from chicken flocks with respiratory and renal problems in China. Thorough genetic and biological investigations of these recombinant viruses have led to speculation regarding their origin, evolution, and control. In order to confirm the previous results and furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
(74 reference statements)
0
17
1
Order By: Relevance
“…Surprisingly, majorities of the New-type 1 strains from other studies were isolated from south China [2,5,15,55]. Recently, another novel genotype VII (GVII-1) was reported [17]. Both these two New-type viruses were identified in our study and the total number of their strains showed New-type was the third most dominant genotype.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Surprisingly, majorities of the New-type 1 strains from other studies were isolated from south China [2,5,15,55]. Recently, another novel genotype VII (GVII-1) was reported [17]. Both these two New-type viruses were identified in our study and the total number of their strains showed New-type was the third most dominant genotype.…”
Section: Discussioncontrasting
confidence: 52%
“…To increase our insight into the comprehensive epidemiological situation and evolutionary trend of IBV in southern China, 27 IBV isolates from 1985 to 2008 in southern China were also used to analyze together. The 43 representative reference strains included the live vaccine strains commonly used and the prevalent strains in China and other countries worldwide, which represented the main well-established lineages and genotypes in recent years in China [17]. Our results indicated that there was a remarkable change in genetic diversity, dominant genotypes, and selection pressure of IBV strains in southern China over the past decade compared with the previous period of 1985–2007.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A potential issue attributed to the recombination is that changes occurring during recombination in the S1 subunit might alter the neutralizing epitopes and result in the appearance of novel IBV serotypes. In addition, recombination events between vaccine and field strains may lead to reversal of virulence and genesis of highly virulent strains [ 44 ]. Therefore, further studies are required to clearly determine the clinicopathobiological features of these viruses in a chicken model.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy adopted by coronaviruses in gene expression regulation facilitates this phenomenon since it depends on discontinuous transcription, which relies entirely on the viral RdRp template-switching property [ 13 , 38 ]. IBV makes no exception: several studies reported recombination events which occurred in field conditions, involving both field and vaccine strains [ 39 , 40 , 41 ]. This evidence has risen some concerns on the potential risk of new recombinant strain emergence, especially when multiple vaccines are administered and/or vaccine strains circulate for a long time.…”
Section: Viral Evolutionmentioning
confidence: 99%